Blood flow restriction as a potential therapy to restore physical function following COVID-19 infection - Wedig, Isaac J.; Durocher, John J.; McDaniel, John; Elmer, Steven J. (Frontiers in Physiology, 2023)
Accumulating evidence indicates that some COVID-19 survivors display reduced muscle mass, muscle strength, and aerobic capacity, which contribute to impairments in physical function that can persist for months after the acute phase of illness. Accordingly, strategies to restore muscle mass, muscle strength, and aerobic capacity following infection are critical to mitigate the long-term consequences of COVID-19. Blood flow restriction (BFR), which involves the application of mechanical compression to the limbs, presents a promising therapy that could be utilized throughout different phases of COVID-19 illness. Specifically, we hypothesize that: 1) use of passive BFR modalities can mitigate losses of muscle mass and muscle strength that occur during acute infection and 2) exercise with BFR can serve as an effective alternative to high-intensity exercise without BFR for regaining muscle mass, muscle strength, and aerobic capacity during convalescence. The various applications of BFR may also serve as a targeted therapy to address the underlying pathophysiology of COVID-19 and provide benefits to the musculoskeletal system as well as other organ systems affected by the disease. Consequently, we present a theoretical framework with which BFR could be implemented throughout the progression from acute illness to outpatient rehabilitation with the goal of improving short- and long-term outcomes in COVID-19 survivors. We envision that this paper will encourage discussion and consideration among researchers and clinicians of the potential therapeutic benefits of BFR to treat not only COVID-19 but similar pathologies and cases of acute critical illness.